The Portrayal of Female Leadership in Caryl Churchill’s Top Girls - Ahmed, Ala B.; Mohamad, Meram S.S. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
This study is an attempt to discuss the notion of feminism in Caryl Churchill’s Top Girls (1982).  The plot mainly surrounds the success of women in a society in which they had been considered as the second sex, as described by the French feminist figure Simone de Beauvoir’s The Second Sex (1949). Her theories on feminism and gender roles have been continuously applied to interpreting literary texts. Therefore, this article tries to integrate de Beauvoir’s theory on feminism into Top Girls. It explores how different generations of women are presented in the play and the way they have struggled with patriarchal rules. Moreover, it tries to explore how the play discusses the themes of; sisterhood, motherhood, abortion, socialism, and capitalism. The study shows how women are perceived in society when they choose a career over motherhood. It discusses the main character’s role as she reaches the top of her career, despite all the obstacles she faces as a female in a patriarchal society.